2011
DOI: 10.1016/j.surg.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways associated with mortality in papillary thyroid cancer

Abstract: Background A better understanding of the molecular mechanisms involved in papillary thyroid cancer (PTC)-associated adverse outcome is needed to effectively manage these patients. Our objectives were to identify molecular pathways associated with unfavorable features and outcome in patients with PTC. Method We performed genome-wide expression (GWE) analysis in 64 PTC human tissue samples. Clinical, pathologic and microarray data were analyzed to identify differentially expressed genes/pathways associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Papillary thyroid cancer thyrocytes have more abundant mitochondria than normal thyrocytes . Furthermore, a genome‐wide expression analysis in PTC identified pathways involved in mitochondrial OXPHOS and fatty acid synthesis as being associated with more aggressive disease . Of the differentially enriched gene sets, three of the 11 that were associated with mortality were related to OXPHOS and mitochondrial metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid cancer thyrocytes have more abundant mitochondria than normal thyrocytes . Furthermore, a genome‐wide expression analysis in PTC identified pathways involved in mitochondrial OXPHOS and fatty acid synthesis as being associated with more aggressive disease . Of the differentially enriched gene sets, three of the 11 that were associated with mortality were related to OXPHOS and mitochondrial metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify genes and pathways associated with mortality in PTC, Nilubol et al (2011) performed genome-wide expression (GWE) analysis in 64 PTC patients and identified the oxidative phosphorylation pathway as one of the significantly perturbed pathways. In addition, Lee and colleagues also showed that the expression of OxPhos gene sets was significantly lower in primary PTC than in matched normal thyroid tissue (Lee et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of in silico target predictions with miRNA and gene expression profiles has been proven to improve the identification of functional miRNA-target gene relationships (Nunez-Iglesias et al, 2010;Ma et al, 2011). As miRNAs act prevalently through degradation of the target genes, expression profiles of miRNA and target genes/transcripts are predicted to be inversely correlated (Bisognin et al, 2012).…”
mentioning
confidence: 99%
“…A recent study using genome-wide expression analysis in PTC samples suggested that the loss of CPSF2 gene expression is correlated with PTC-associated mortality (18). Another study reported that CPSF2 knockdown increases cellular invasion and expression of thyroid cancer stem-like markers CD44 and CD 133, which could promote tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The exact function of CPSF2 is still unknown, while its presence is essential for the pre-mRNA maturation process (15)(16)(17). On the basis of genome-wide expression analysis, a recent study identified that the loss of CPSF2 gene expression is related to PTC-associated mortality in PTC samples (18). Another study reported that CPSF2 knockdown increases cellular invasion and expression of the thyroid cancer stem-like markers CD44 and CD133, and that the loss of CPSF2 gene expression is also associated with more advanced PTC (17).…”
Section: Introductionmentioning
confidence: 99%